Lower endoscopic ultrasound in preoperative evaluation of rectosigmoid endometriosis - James, Theodore W.; Fan, Y. Claire; Schiff, Lauren D.; Gangarosa, Lisa M. (Endoscopy International Open, 2019)
Background and study aims Endometriosis affects a significant proportion of reproductive-aged women and involves the bowel in up to one-third of patients with the condition. Lower endoscopic ultrasound (LEUS) in assessment of endometriosis of the rectosigmoid colon was first described 20 years ago in European populations. The current study aimed to describe the diagnostic characteristics of this imaging modality at a tertiary US referral center in a large cohort and its impact on surgical planning. Patients and methods This was a retrospective cohort study of adult women evaluated for rectosigmoid endometriosis by LEUS at an American tertiary referral center between January 2003 through June 2017. The reference standard for rectosigmoid endometriosis was surgical evaluation regardless of whether tissue was obtained for histologic evaluation. Two separate analyses were run; one comparing EUS to laparoscopic findings and another comparing EUS to histologic findings. Results LEUS demonstrated a positive predictive value (PPV) of 93.8 % (CI:68.1,99.1) and negative predictive value (NPV) of 96.4 % (CI:87.8,99.0) in the diagnosis of rectosigmoid endometriosis. Test sensitivity was 88.2 % (CI:63.6,98.5) and specificity was 98.2 % (CI:90.1,99.9). Overall diagnostic accuracy of the test was 95.8 % (CI:88.1,99.1). Conclusions In this large cohort of women at an American tertiary referral center undergoing evaluation for rectosigmoid endometriosis, LEUS demonstrated high PPV and NPV as well as excellent diagnostic accuracy. In addition, the LEUS findings provided important information to the referring gynecologic surgeon. This minimally-invasive imaging modality should be utilized in preoperative evaluation of women undergoing surgery for suspected or known endometriosis.